Corrosion understanding the basics - Davis, J. R. (ASM International, 2000)
Annotation As the title suggests, this is an introductory book covering the basics of corrosion. It is intended primarily for professionals who are not corrosion experts, but may also be useful as a quick reference for corrosion engineers. Included in the 12 chapters are discussions of the physical principles and characteristics of corrosion, help in recognizing and preventing corrosion, and techniques for diagnosing corrosion failures
Keywords: Corrosion and anti-corrosives.; Metals -- Defects.; elektronické knihy; electronic books